El maltrato infantil y su incidencia en el comportamiento de los niños y niñas de educación inicial 1 del centro infantil del buen vivir “Mi Pequeño Cielo” de la ciudad de Quito, período lectivo 2013-2014”. Lineamientos alternativos - Vaca Salazar, Amparo del Rocío (2014)
This investigation is about “CHILD ABUSE AND ITS IMPACT ON THE INITIAL EDUCATIONAL CHILDREN BEHAVIOR OF “MI PQUEÑO CIELO” GOOD LIVING CHILD CENTER, QUITO CITY, PERIOD 2013-2014. ALTERNATIVE GUDELINES. The General Objective was to Determine Child Abuse and its impact on the Initial Educational Children Behavior of “MiPequeñoCielo” Good Living Child Center, Quito city, Period 2013-2014. The Methodology used was based primarily on the scientific method, Inductive, Deductive, Analytical, Synthetic, Descriptive Model Description. The Techniques of the research instruments are applied to Survey Parents to set the Child Abuse and Observation Listing Behavior type to establish the children present. From the survey results it is concluded that: 49% of respondents Parent Family states that a negative attitude to talk with the child, 19% yell, 18% to punish him and hit the 14%. Also 31% of respondents Parents, show that the type of abuse that affects the children is psychological abuse, 27% is Sexual Abuse, 24% is the abuse F musician, and 18% is the Verbal Abuse. In support of the research work is applied Observer the following result was obtained: 41% of boys and girls 1 Initial Education Children's Center "My PequeñoCielo" has a behavior Liabilities, 35% had Assertive Behavior, and Aggressive Behavior has 24%. The problematic or inappropriate behavior of a child is a sign that something is not right. It is especially important to pay attention because this behavior Passive behavior is not appropriate and not express their needs, thoughts and feelings can not be expressed in a clear and straightforward, just generate aggression against himself. It is necessary to evaluate and propose alternative guidelines aimed at parents and teachers for the problems caused by child abuse and improve the behavior of girls and boys